2019
DOI: 10.1097/j.pain.0000000000001577
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory predictors of response to pregabalin in painful chemotherapy-induced peripheral neuropathy: a randomized, placebo-controlled, crossover study

Abstract: Supplemental Digital Content is Available in the Text. Baseline mechanical pain threshold does not predict analgesic response to pregabalin in painful chemotherapy-induced peripheral neuropathy caused by docetaxel, paclitaxel, or oxaliplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…Several drugs have been reported for treating CIPN. In these reports, calcium and magnesium, goshajinkigan, duloxetine, vitamin B12, pregabalin, and gabapentin were used [41][42][43][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. However, calcium/magnesium, goshajinkigan, and gabapentin were found to be ineffective at treating CIPN in the largest double-blind randomized controlled trials (RCTs) for each drug.…”
Section: Discussionmentioning
confidence: 99%
“…Several drugs have been reported for treating CIPN. In these reports, calcium and magnesium, goshajinkigan, duloxetine, vitamin B12, pregabalin, and gabapentin were used [41][42][43][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. However, calcium/magnesium, goshajinkigan, and gabapentin were found to be ineffective at treating CIPN in the largest double-blind randomized controlled trials (RCTs) for each drug.…”
Section: Discussionmentioning
confidence: 99%
“…On a larger scale, post hoc analysis of clinical trial data revealed that pregabalin had no benefit in patients with HIV neuropathy but provided pain relief in a patient subgroup characterized by severe pinprick hyperalgesia. 32 A more recent study of patients with chemotherapy-induced neuropathy found that mechanical pain thresholds were not predictive of response to pregabalin, though the number of patients exhibiting mechanical hypersensitivity was low, 33 and the former study noted that only those patients with the most severe pinprick hyperalgesia benefited, whereas those with mild/moderate hyperalgesia did not. Baron and colleagues proposed that these patients are represented by the mechanical cluster (Figure 1) and that central sensitization is the predominant pathophysiological mechanism.…”
Section: Calcium Channel Modulatorsmentioning
confidence: 98%
“…The Patient Neurotoxicity Questionnaire (PNQ) scores in the pregabalin group were better than those in the duloxetine group (improving the PNQ scores : pregabalin : 90% vs duloxetine : 31%, p value < 0.001) 33) . Some adverse events were reported in the Drug treatment for CIPN above RCTs (somnolence 22.5 -88%, dizziness 17.5 -68%, ataxia 5.0%, and diplopia 2.5%) 32,37) .…”
Section: Pregabalinmentioning
confidence: 99%